Ovarian Cancers : Advances through International Research Cooperation (GINECO, ENGOT, GCIG) - Pujade-Lauraine, Eric; Ray-Coquard, Isabelle; Lécuru, Fabrice (Springer International Publishing : Imprint: Springer, 2017)
This book provides an overview of the latest developments in the concepts and management of ovarian cancer. The new data presented throughout opens the way to radically different therapeutic approaches. Surgery remains the core of ovarian cancer treatment, but its ultimate goal and the standard surgical procedure have evolved, giving rise to the question of how to label expert centers for debulking surgery. Neo-adjuvant chemotherapy is becoming more popular and is also a new field for testing novel drug combinations. Over recent years, ovarian cancer management has embraced molecular biology. It is now more correct to talk about cancers of the ovary rather than ovarian cancer, since it is not a unique disease but several entities with different molecular drivers. The significant advances in drugs targeting the microenvironment or the tumor cell DNA repair mechanisms are presented in detail together with exciting future perspectives. All these advances would not have been possible without collaborative groups such as the GINECO group in France and their integration in wider clinical research networks at the European (ENGOT) and international (GCIG) level.
Keywords: Medicine.; Gynecology.; Oncology.; Pathology.; Reproductive medicine.; Surgical oncology.; elektronické knihy; electronic books